Práticas de alfabetização em séries iniciais em duas escolas do ensino fundamental do município de Vitória - Costa, Kaira Walbiane Couto (2010)
This paper is about a case study which is aimed at analyze the literacy practices of the teachers from two schools of the Municipal Teaching System of Vitória/ES. Literacy is seen as a social and cultural practice which involves the production of oral and written texts, reading and knowledge about the writing system. Supported by this concept we tried to discover which literacy dimensions are more privileged by the literacy teachers with the objective of knowing the concept which guides the teachers’ practices. Participative classroom observation, interviews, audio recordings and photographs were used to collect data. Based on the data collection the events destined to the teaching of the mother tongue were selected and the conceptual evidences which permeate the teachers’ practices organized. For the analysis of the events, the theoretical presuppositions of the bakhtiniana’s philosophy of languages were used, considering different authors who follow the same perspective as well. The literacy teachers’ practices are seen as having similarities once the knowledge teaching of the writing system, reading and text production were privileged in the two classrooms. However, the emphasis on the first knowledge highlights that literacy happens as a process of the acquisition of the reading and writing skills - decodification and codification